SOSIALISASI PENYUSUNAN ANGGARAN PENGADAAN KOLAM IKAN BERBASIS BIOFLOK DI KABUPATEN PESAWARAN PADA PROGRAM PEJUANG MUDA KEMENSOS - Lego Waspodo (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
The purpose of this community service activity is to increase the understanding of Pesawaran Regency Young Warriors on budgeting according to the 2021 Ministry of Finance input cost standards and to improve the skills of Young Warriors in preparing budgets that are in accordance with the Ministry of Finance input cost standards for 2021. Budgeting training is conducted at the Social Service Pesawaran district, Lampung province. Training on budget preparation to complete project proposals was attended by all Young Fighters in Pesawaran District consisting of 9 students. The nine students came from various universities as follows: Lamung University, Siliwang University, Darmajaya University, and Semarang State University. Based on the results of sending questionnaires before and after the training, it can be concluded that the understanding of the training participants before and after the training has increased. After attending the training the participants have a good understanding of the meaning of the budget and after attending the training the participants are able to prepare a project budget properly and in accordance with the ministry of finance's 2021 entry fee standards.